Interaction between pancreatic fluid and three different hemostatic agents: an in-vitro study (Annals of Medical Research, 2021)
Aim: Although recent developments in surgery led to mortality reduction under 2%, postoperative pancreatic fistula (POPF) remains high reported from 20% up to 40%. Primary aim of the present in-vitro study was to determine the interaction between pancreatic fluid and three different hemostatic agents.Material and methods: Three different hemostatic agent; fibrin sealant Tisseel, Floseal and Ankaferd Blood Stopper (ABS) were mixed in tubes with pancreatic fluid in equal proportions. The length of the gel aggregate of each sample which covers the pancreatic fluid in the tube was measured as mm and thereafter statistically compared.Results: Tisseel significantly formed an intensely thicker gel than Floseal and ABS (Tisseel vs FloSeal; P0.0001, Tisseel vs ABS; P0.0001). Further, the thickness of the gel formation was significantly higher in FloSeal-pancreatic fluid mixture than the ABS-pancreatic fluid mixture (P0.0001). Under light microscope, Tisseel formed a much more homogenous and dens mixture than Floseal and ABS.Conclusion: Tisseel fibrin sealant has beneath its hemostatic properties also the potential of preventing pancreatic fistula development. Further in-vitro and in-vivo studies are needed to reach a definitive conclusion.Keywords: Hemostasis; Pancreatic Fistula; Hemostatic Agents; Interaction.
Keywords: Hemostasis; Pancreatic Fistula; Hemostatic Agents; Interaction.